Chronic Kidney Disease: A Case Series (Part 5) (Advancements in Homeopathic Research, 2024)
After successful demonstration in their previous  four publications that patients of chronic kidney  disease (CKD) and acute renal failure (ARF) can be  managed by homoeopathic treatment, Gupta et. al. herewith put forth another episode of this case series.  This fifth case series is on successful management of  CKD patients by maintaining their serum creatinine  level and eGFR within a reasonable range, delaying  further deterioration and improving their quality  of life for a considerable period of time without  haemodialysis. The first two cases in this series are  of 62-year and 59-year old hypertensive, diabetic  males with CKD in whom S. Creatinine level was  maintained for about 7 and 3 years respectively. In  third case of a 47-year old hypertensive, non-diabetic  male, S. Creatinine level was maintained without  haemodialysis for more than 2 years.
Keywords: Haemodialysis (HD); peritoneal dialysis (PD); chronic kidney disease (CKD); chronic renal failure (CRF); end stage renal disease (ESRD); serum urea; blood urea nitrogen (BUN); serum creatinine; estimated glomerular filtration rate (eGFR); renal transplant; homoeopathic treatment